(untitled) (Andamios, Revista de Investigación Social, 2025)
In recent years, the debate on the automation of production has intensified, which among its many aspects contains an under-addressed one, which is fundamentally normative in nature. In discussion with a series of current approaches that advocate full automation of production to give rise to a post-capitalist society, the objective of this article is to critically think about the ethical-political limits of automation. On the one hand, although automation is a means to achieve greater free time and material abundance, these goals are not absolute and may contradict other equally desirable objectives. On the other hand, current automation follows a pattern that would threaten certain human capacities whose development is essential for an emancipatory policy.